MENINGKATKAN KEMAMPUAN LOMPAT JAUH GAYA JONGKOK DENGAN MENGGUNAKAN MEDIA BAN - Irsan Kahar (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This research is a classroom action research (CAR) which aims to improve the ability to jump long squat style using tires. This research was conducted in four stages, namely planning, implementation, observation and reflection. The sample of this research is the fourth grade students of SD Negeri 10 Muarente, Luwu Regency. The location of this research was carried out at SD Negeri 10 Murante, Luwu Regency, during the research April-May 2022, the sample of this study was 20 4th grade students of SD Negeri 10 Murante, Luwu Regency, consisting of 11 male students and 9 female students. This classroom action research instrument is a practical test (Psychomotor), attitude (Affective), Knowledge test (Cognitive). Based on the results of the study, the percentage in the first cycle was 65% with sufficient category and increased in the second cycle by 95% very well. Based on the evaluation results in cycle I and cycle II. The results of data analysis showed that there was a significant increase in the long jump ability of the squat style using tires/rubber media long jump squat style of fourth grade students of SD Negeri 10 Murante, Luwu Regency.